THE MODERATION EFFECT OF COMMITMENT TO SUPERVISOR AND INTERNET EXPERTISE ON WORK STRESSOR AND EMPLOYEE CYBERLOAFING: THE STUDY ON EMPLOYEE OF LOCAL GOVERNMENT OF SURAKARTA - Runing S., Hunik Sri; Cahyadin, Malik (Journal of Indonesian Economy and Business, 2012)
The aims of this study are to examine the effect of work stressor on employee cyberloafing, to examine the influence of the commitment to supervisor on employee cyberloafing, to examine the influence of work stressor on employee cyberloafing with commitment to supervisor as a moderating variable, and to examine the influence of work stressor on employee cyberloafing with internet expertise as a moderating variable.Through purposive sampling method, 199 samples were taken from employees of local government. The employees have an internet access when doing their task. Data analysis using hierarchical regression analysis show that hypothesis 1a, 1b and 3f were supported.The role ambiguity and role conflict has a significant positive effect on cyberloafing. It means, the higher the role ambiguity and the role conflict are, the higher employeecyberloafing will be. Further, the higher the employee overload is, the higher the employee cyberloafing will be if they have high internet expertise.Keywords: role ambiguity, role conflict, role overload, commitment, and cyberloafing.